ANALISIS PRODUKTIFITAS PENYABLONAN KAOS MENGGUNAKAN METODE MARVIN E.MUNDEL - Frido Farandi Pradana; Andung Jati Nugroho (Jurnal DISPROTEK, 2021)
Competition among companies engaged in convection is measured by the level of productivity of the company, therefore each company is required to improve its performance more effectively and efficiently so as to achieve the goals expected by the company. This research was conducted in creamber Cloth Convection printing and sewing shirts aimed at measuring the productivity value by establishing January 2019 as a base period with the Marvin E Mundel method with 6 indicators namely: deflactor, constant price, RIP, Aggregate Output, Partial productivity index and Productivity Index Total. Based on the results of productivity measurements during the measurement period by setting the acquisition value obtained from the measurement results, the highest material productivity index was reached in May with a value of 108.68% and the lowest in June with a value of 94.56%, while the labor productivity index the highest employment was in May 2019 with a value of 121.47% and the lowest in June was 87.76%, the highest energy productivity index in May was 121.63% and the lowest in June 2019 was 87.87%, the Index the highest depreciation productivity in May was 121.76% and the lowest in June with a value of 87.96%, the total productivity index which increased from the base month in May was 110.99%, while the total productivity index experienced a decrease compared to the base month in June with a value of 93.13%.